Altitude and fungal diversity influence the structure of Antarctic cryptoendolithic Bacteria communities. Issue 5 (26th August 2019) - Coleine, Claudia; Stajich, Jason E.; Pombubpa, Nuttapon; Zucconi, Laura; Onofri, Silvano; Canini, Fabiana; Selbmann, Laura
Summary: Endolithic growth within rocks is a critical adaptation of microbes living in harsh environments where exposure to extreme temperature, radiation, and desiccation limits the predominant life forms, such as in the ice‐free regions of Continental Antarctica. The microbial diversity of the endolithic communities in these areas has been sparsely examined. In this work, diversity and composition of bacterial assemblages in the cryptoendolithic lichen‐dominated communities of Victoria Land (Continental Antarctica) were explored using a high‐throughput metabarcoding approach, targeting the V4 region of 16S rDNA. Rocks were collected in 12 different localities (from 14 different sites), along a gradient ranging from 1000 to 3300 m a.s.l. and at a sea distance ranging from 29 to 96 km. The results indicate Actinobacteria and Proteobacteria are the dominant taxa in all samples and defined a 'core' group of bacterial taxa across all sites. The structure of bacteria communities is correlated with the fungal counterpart and among the environmental parameters considered, altitude was found to influence bacterial biodiversity, while distance from sea had no evident influence.